THE EFFECTIVENESS OF PEER CORRECTION TO GRAMMATICAL ACCURACY IN STUDENTSâ WRITING (A Study at the Second Semester Students of English Education Study Program of STKIP PGRI Bandar Lampung in the Academic Year of 2013/2014) - Maximilian, Aksendro (Lentera: Jurnal Ilmiah Kependidikan, 2014)
The purpose of this research was to investigate whether or not peer correction had an effect in improving grammatical accuracy in studentsâ writing. The method used in this research was pre-experimental design, especially in the form of one-group pretest-posttest design. The subject of this research was the second semester students of English Education Study Program of STKIP PGRI Bandar Lampung in the academic year 2013/2014. The instument used in this research was a writing test. The students were taught by using peer corection technique. The pre-test was given before the treatments to see the starting score. After giving the treatment, post test was given. The results of the research were analyzed by using t-test for dependent samples. From the result of t calculation, t count was higher than t table (13.85 > 2.04). Thus, the alternative hypothesis (Ha) was accepted and the null hypohesis (H0) was rejected. It also can be seen that the mean score in the post-test was higher than the mean score in the pre-test. In other words, there was a significant difference between the mean score in the pre-test and the mean score in the post-test. Therefore, it was concluded that there was a significant positive effect of applying peer correction technique to grammatical accuracy in studentsâ writing.